Evaluating the affordances of wearable technology in education. (2019) - Attallah, Belsam; Il-agure, Zakea
Wearable technology, or the so-called wearable computing, is increasingly becoming popular in learning and teaching activities. Higher education is particularly benefitting from the advanced applications of this emerging technology, owing to the mature utilisation of the features and facilities presented by wearable devices. Essential factors like students' interactivity and engagement in learning activities have found to be easily achieved when effectively utilising this evolving technology by academic organisations. This paper surveys the information and experiments published recently on wearable technology in higher education and its acceptance factors by consumers according to the Technology Acceptance Model (TAM). Alongside the academic advantages of this technology, the paper demonstrates the limitations and negative aftereffects accompanying its applications. The outcomes of this research revealed that there are a considerable number of restrictions limiting the wider application of this technology and its acceptance in higher education, which should be analysed with appropriate solutions proposed.